DEBT DECISION-MAKING: OVERCONFIDENCE, ANCHORING, AND LOSS AVERSION WITH RISK PERCEPTION AS MEDIATION - Feby Santika Sari; Ida Subaida (Jurnal Media Ekonomi (JURMEK), 2026)
Purpose: Psychological biases are believed to play an important role in debt decision-making among SME players. This study aims to analyze the effect of overconfidence, anchoring, and loss aversion on debt decision-making with risk perception as a mediating variable among rengginang SME players in Situbondo Regency. Research Methodology: This study employed a quantitative approach using a structured questionnaire distributed to 63 rengginang MSME players in Gelung Village, Situbondo Regency, selected through purposive sampling. Data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) with SmartPLS software. Results: Overconfidence had no significant effect on risk perception but significantly affected risk perception, anchoring had no direct effect on debt decision-making, and risk perception did not mediate overconfidence, fully mediated anchoring, and partially mediated loss aversion on debt decision-making. Conclusions: Psychological biases work through different mechanisms in influencing debt decision-making. Overconfidence works directly, anchoring works entirely through risk perception, and loss aversion works through both pathways simultaneously. Limitations: This study is limited to rengginang MSMEs in Gelung Village, Situbondo Regency, and did not classify respondents by debt source type despite considerable variation in the field. Contributions: This study contributes to the development of behavioral finance literature in the context of traditional rural MSMEs that have rarely been studied. Furthermore, the field findings of considerable variation in debt source types ranging from banks and pegadaian to informal debt to rice mill owners with a harvest-based repayment system without interest open new contribution opportunities for future research to explore debt source type as a mediating variable that has never been previously examined in the MSME behavioral finance literature.